1998
DOI: 10.1016/s0266-7681(98)80009-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Segmental Carpal Tunnel Pressures with Changes in Hand and Wrist Positions in Patients with Carpal Tunnel Syndrome and Controls

Abstract: We investigated pressures at 1 cm intervals along the carpal tunnel in 39 patients with carpal tunnel syndrome (CTS) and 12 controls. Pressures were measured for relaxed and gripping hand positions in combination with neutral, extended, and flexed wrist positions. Patient pressures exceeded control pressures, were below the previously reported 30 mmHg threshold for four of five locations in the relaxed neutral position and were typically greater in extension than in flexion. In the neutral position, both patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 25 publications
5
45
1
2
Order By: Relevance
“…Similarly, Luchetti et al showed that carpal tunnel pressure was higher when the wrist was in extension compared to flexion. 13 You et al investigated the relationships between the clinical symptom severity scales and nerve conduction measurements in CTS and found them to be significant. 14 This may explain the conflicting results concerning the provocative tests.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Luchetti et al showed that carpal tunnel pressure was higher when the wrist was in extension compared to flexion. 13 You et al investigated the relationships between the clinical symptom severity scales and nerve conduction measurements in CTS and found them to be significant. 14 This may explain the conflicting results concerning the provocative tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although upper-extremity musculoskeletal disorders have not been directly associated with this muscle group, it was chosen because the finger flexor tendons travel through the carpal tunnel and increased force on these tendons has been shown to increase carpal tunnel pressure (24,25). A surface EMG electrode with dual 8-millimeter diameter bipolar silver-silver chloride surfaces, an interelectrode distance of 22 millimeters, and onsite preamplification with a gain of 35 (EQ Inc, Chalfont, PA, USA) was interfaced with a portable data logger collection system (Tattletale Model 5F-LCD, Onset Computer Corp, Pocasset, MA, USA).…”
Section: Direct Exposure Assessmentmentioning
confidence: 99%
“…KTS'de en çok tercih edilen volar destekli nötral splintlerdir (6)(7)(8). Bileğin nötral pozisyonda splintlenmesindeki amaç, nötral pozisyonda karpal tü-nel hacminin artırılması ve median sinir üzerindeki basıncın azaltılmasıdır (7).…”
Section: Introductionunclassified
“…Bileğin nötral pozisyonda splintlenmesindeki amaç, nötral pozisyonda karpal tü-nel hacminin artırılması ve median sinir üzerindeki basıncın azaltılmasıdır (7). El bileğinin ekstansiyon hareketindeki artış karpal tünel basıncının daha fazla artmasına neden olur (8).…”
Section: Introductionunclassified